Detection of SARS-CoV-2 and HHV-8 from a large pericardial effusion in an HIV-positive patient with COVID-19 and clinically diagnosed Kaposi sarcoma: a case report - Ryan R. Yanes; Greco Mark B. Malijan; Lyka Kymm Escora-Garcia; Stephanie Angel M. Ricafrente; Mary Jane Salazar; Shuichi Suzuki; Chris Smith; Koya Ariyoshi; Rontgene M. Solante; Edna M. Edrada; Kensuke Takahashi (Tropical Medicine and Health, 2022)
Abstract Background Pericardial effusion is a late manifestation of HIV more commonly observed in individuals with depressed CD4 counts. Although Mycobacterium tuberculosis remains to be one of the most frequently identified pathogens in the pericardial fluid among people living with HIV, less commonly described etiologies include SARS-CoV-2 that causes coronavirus disease and human herpesvirus-8 which is associated with Kaposi sarcoma. Isolation of more than one pathogen in normally sterile sites remains challenging and rare. We report the first documentation of both SARS-CoV-2 and HHV-8 in the pericardial fluid. Case presentation We present the case of a young man in his 20s with a recent history of clinically diagnosed pulmonary tuberculosis who was admitted for progressive dyspnea and cough. He had multiple violaceous cutaneous lesions on the face, neck, and trunk and diffused lymphadenopathies. He tested positive for SARS-CoV-2 on admission. The patient was clinically diagnosed with pneumonia, Kaposi sarcoma, and HIV/AIDS. Empiric broad spectrum antimicrobial regimen was subsequently initiated. HIV with low CD4 count was confirmed during hospitalization. Echocardiography revealed a large pericardial effusion, in impending cardiac tamponade. Frond-like fibrin strands, extending to the parietal pericardium, were also observed. Pericardiostomy yielded hemorrhagic, exudative effusion with lymphocytic predominance. SARS-CoV-2 and HHV-8 were detected in the pericardial fluid, and bacterial, fungal, and tuberculous studies were negative. The patient had clinical improvement after pericardial drainage. However, despite our best clinical care, he developed a nosocomial infection leading to clinical deterioration and death. Conclusion Detection of SARS-CoV-2 and HHV-8 in the pericardial fluid is rare, and interpretation of their significance in clinical care is challenging. However, coronavirus disease and Kaposi sarcoma must be considered and adequately addressed in immunocompromised adults presenting with large pericardial effusion.